EFFECT OF THE GUIDED INQUIRY LEARNING MODEL ASSISTED BY SCIENTIFIC WORKSHEET TOWARD CRITICAL THINKING SKILLS - Beta Kurnia Illahi; Yurnetti Yurnetti (Department of Physics Universitas Negeri Padang, 2023)
The learning model is still teacher-centered and needs to use teaching materials that support the learning process, which causes students' critical thinking skills to be underdeveloped. One learning model that can improve students' critical thinking skills is a learning model that involves active and student-centered students is the guided inquiry learning model. The applied guided inquiry learning model must have supporting media and teaching materials. Teaching materials that are practical and operational in the guided inquiry learning model are scientific worksheets. This study aims to determine the effect of the guided inquiry learning model assisted by scientific worksheets on the critical thinking skills of class XI natural science students. This research method is quasi-experimental with a randomized control group-only design. The population of this research is class XI natural science one of the Islamic senior high school in West Sumatra, Indonesia. Sampling was carried out using a purposive sampling technique in which the research results concentrated on critical thinking skills taken through critical thinking questions in the form of essays. The data in this study were analyzed using descriptive analysis and two average similarity tests. Data analysis showed thatc ,Then a t-test was carried out with the results of the t-count test of 3.47 with t-table 1.99 indicating that t-count is outside the acceptance area of ​​Ho, meaning that Hi is accepted, that is, there is a significant influence of the Scientific worksheet on students' critical thinking skills.